FUTURE-PROOF ENGINEERING: A CROSS-FUSION OF DISCIPLINES IN INNOVATIVE EDUCATION - Chen , Mei Ling (Top Educational Review Journal (TERJ), 2024)
In response to the need for cultivating high-quality comprehensive talents and adapting to national economic and social development, colleges and universities are embracing a multi-disciplinary cross-fusion cultivation mode in their undergraduate education reform efforts. This mode aligns with the Ministry of Education’s "New Engineering Research and Practice" initiative, which emphasizes the integration of engineering disciplines with other fields to advance interdisciplinary training and foster versatile engineering talents. The "Guidelines for New Engineering Research and Practice Projects" further underscores the importance of this approach in promoting a comprehensive engineering education concept and exploring innovative models for multi-disciplinary cross-fusion engineering talent developent. In light of these policies, local educational institutions have initiated transformative processes to align with the changing landscape. This paper delves into the implications and strategies associated with this shift in educational paradigms, shedding light on the evolution of higher education towards a more integrated and forward-thinking approach.